2005
DOI: 10.1055/s-2005-865894
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Plant Cell Wall Invertase in Roots of Arabidopsis Leads to Early Flowering and an Increase in Whole Plant Biomass

Abstract: In order to enhance sink strength, we expressed a heterologous plant cell wall invertase (CrCIN1) under the control of a root-specific promoter (ppyk10) in Arabidopsis thaliana. Slightly elevated apoplastic invertase activity resulted in apparent phenotypic changes. Transgenic plants developed more secondary roots and subsequently, possibly because of a higher capacity to acquire nutrients, a higher shoot and whole plant biomass. Furthermore, an early flowering phenotype was detected. The data presented here d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 51 publications
1
17
0
1
Order By: Relevance
“…In contrast, transgenic tobacco plants expressing the apoplastlocated yeast invertase with a seed-specific promoter did not show increased accumulation of storage products in the oilseeds, even with additional overexpression of hexokinase, indicating no change in the sink strength of these storage sinks (Tomlinson et al, 2004). In Arabidopsis, the root-specific expression of yeastderived apoplastic invertase had no detectable effect on the plant biomass as well (von Schweinichen and Bü ttner, 2005). In contrast, Arabidopsis plants expressing an apoplastic invertase of Chenopodium rubrum with the root-specific pyk10 promoter showed only slightly enhanced invertase activity and no changes in the soluble sugar contents, but there was an indirect influence on the whole plant development and an increased total plant biomass (von Schweinichen and Bü ttner, 2005).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In contrast, transgenic tobacco plants expressing the apoplastlocated yeast invertase with a seed-specific promoter did not show increased accumulation of storage products in the oilseeds, even with additional overexpression of hexokinase, indicating no change in the sink strength of these storage sinks (Tomlinson et al, 2004). In Arabidopsis, the root-specific expression of yeastderived apoplastic invertase had no detectable effect on the plant biomass as well (von Schweinichen and Bü ttner, 2005). In contrast, Arabidopsis plants expressing an apoplastic invertase of Chenopodium rubrum with the root-specific pyk10 promoter showed only slightly enhanced invertase activity and no changes in the soluble sugar contents, but there was an indirect influence on the whole plant development and an increased total plant biomass (von Schweinichen and Bü ttner, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In Arabidopsis, the root-specific expression of yeastderived apoplastic invertase had no detectable effect on the plant biomass as well (von Schweinichen and Bü ttner, 2005). In contrast, Arabidopsis plants expressing an apoplastic invertase of Chenopodium rubrum with the root-specific pyk10 promoter showed only slightly enhanced invertase activity and no changes in the soluble sugar contents, but there was an indirect influence on the whole plant development and an increased total plant biomass (von Schweinichen and Bü ttner, 2005). The authors observed a similar phenotype when the extracellular-located yeast invertase was driven under a meristem-specific promoter, which was observed in several other studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The rol genes of Agrobacterium rhizogenes are known to affect plant hormone metabolism and/or sensitivity; therefore, these are suitable tools to modify plant development (van der Salm et al 1996), including apical dominance, enhanced rooting, accelerated flowering, and short life span. von Schweinichen and Büttner (2005) have reported that an increase in root mass and, consequently, in root surface area, allows the effective absorption of nutrients from the medium (soil), resulting in enhanced development. Although enhanced rooting in rol transformed plants positively affects plant architecture, whether or not this improves root profile to absorb more nutrients in water-deficient regions is yet to be proven.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enhance sink strength, heterologous plant cell wall invertase (CrCIN1) was transformed into Arabidopsis thaliana. Under the control of a root-specific promoter, and the transgenic plants developed more secondary roots and subsequently, a higher shoot and whole plant biomass, furthermore flower in advance (Schweinichen and Büttner 2005). By expressing a CIN under a meristem-specific promoter, Arabidopsis thaliana increased CIN activity, caused accelerated flowering, elevation of the number of siliques which result from enhanced branching of the inflorescence and an increase in seed yield by nearly 30 % (Heyer et al 2004).…”
Section: Introductionmentioning
confidence: 98%